Investigation on Soda-Anthraquinone Pulping of Rapeseed Straw - Said mohammad Mazhari mosavi (Regional Information Center for Science and Technology (RICeST), 2009)
This research is aimed to study the possibility of rapeseed straw (Hayolla401) pulping and its paper characteristics, using Soda-AQ process. The average fiber length was found 1.04 millimeter and the average fiber diameter, lumen and thickness were found 28.00, 19.09, and 4.91 micrometer, respectively. Cellulose, lignin, extractive material (acetone solved) and ash were measured 41.66, 16.00, 1.63, and3.46 percent, respectively. Cooking condition was determined as follow: Soda as 16, 18, and 20 percent on the basis of rapeseed dry straw, temperature was set at 175 and 185 Cº, cooking time was set at 40 and 70 minutes, and straw to liquid ratio was set at 1/8. The amount of anthraquinone added to cooking liquor was 0.2%, based on rapeseed dry straw. Using severe cooking factors caused reduction of yield and Kappa number in both methods. Refining was performed on selected pulps in order to reach 35025     (ml,CSF) freeness. The 60 gr/m² hand sheets were made in order to determine mechanical strength and physical properties. Average thickness, density and bulk is measured at 86.4µ, 0.69gr/cm³ and 1.44cm³/gr respectively. Average tear index, burst index, breaking length and tensile indexare measured at 4.6 mN.m²/gr, 3.5 kpa.m²/gr, 7.4km and 72.6Nm/g respectively.